Requirements For The Implementation Of The Contemporary Empowerment Strategy Of The Labor In Business Organizations - فياض, لينا (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aimed to clarify the reality of working environment at Tishreen University and it's fitness to the requirements of the application of the contemporary empowerment in business organization, by assessing the reality of the delegation of authority delegation of decision -making participation، independence of work and work environment، the researcher relied on the deductive approach as a method of thinking The descriptive approach has a procedural approach to determine the availability of the dimensions of the contemporary empowerment strategy at Tishreen University. The researcher distributed a questionnaire to 313 workers. The study found that the minimum arithmetic average of the responses of the respondents to the statements that measure the delegation of employees' participation decision-making is 2.58، which is less than the average of neutrality (3)، which shows that the university does not make decisions in the least. Levels according to the responses of the sample members، and this affects the mechanism of work at these levels، which is reflected on their level of performance. Then some proposals were presented، the most important of which is the need for the university to provide the optimal participation of decision-making among its staff، as this will reflect on their performance and enable them to accomplish their work.